EFFECTIVENESS OF THE E-MODULE 7E CYCLE INTEGRATED TECHNOLOGICAL KNOWLEDGE IN IMPROVING THE SCIENTIFIC REASONING SKILLS OF PROSPECTIVE TEACHER STUDENTS - Dea Mustika; Laili Rahmi; Bahril Hidayat; Karmelia; Kayla Addina (Jurnal Cakrawala Pendas, 2026)
Scientific reasoning skills are fundamental skills that prospective teachers must possess to design and implement ideal science learning. However, science learning taught to students focuses predominantly on mastery of concepts and does little to train students' scientific reasoning skills. The purpose of this study was to analyze the effectiveness of the 7E cycle e-module integrated on technological knowledge in improving the scientific reasoning skills of prospective elementary school teachers. The method used was a quasi-experiment with two sample classes consisting of an experimental class (40 students) and a control class (38 students). The research instrument was a scientific reasoning test consisting of 20 questions. The data were analyzed using the N-Gain test, normality test, homogeneity test, and hypothesis testing using an independent sample t-test. The results showed that the data were normally distributed and homogeneous. The N-Gain value for the experimental class was 0.71, which is in the high category, while that for the control class was 0.42, which is in the moderate category. The t-test results showed a significance value of 0.000 (p < 0.02) with a calculated t-value of 7.84. This means that there was a significant difference in the improvement of scientific reasoning skills between the two classes. The conclusion is that the 7e cycle e-module integrated on technological knowledge is effective in improving the scientific reasoning abilities of prospective teacher students and has the potential to be an alternative teaching material for science learning in higher education